The Study of Conversational Style and Preference Structure in Deddy Corbuzier’s Podcast: Anies Baswedan Episode - Desi Amalia; Juli Rachmadhani Hasibuan; Lidiman Sahat Martua Sinaga (TRANSFORM : Journal of English Language Teaching and Learning, 2021)
This study discussed about conversational style and preference structure in Deddy Corbuzier’s Podcast: Anies Baswedan Episode. The objectives of the study were to find the conversational style used by Deddy Corbuzier and Anies Baswedan in the podcast, the preference structure used by Anies Baswedan as the second speaker, and the dominant types of preference structure used in the podcast. This study used the descriptive qualitative method. This study used the theories from Tannen (2005) about conversational style and Levinson (1983) about preference structure. The results of this study can be concluded as: First, the conversational style used by the speakers was high-involvement style (personal topic, faster rate of speech, tell more stories, and used higher pitch). Second, the types of preference structure used by Anies Baswedan as the second speaker was preferred responses or positives responses (expected answer, agreement for assessment, and agreement for proposal). Third, the dominant types of preference structure occurred in the podcast was preferred responses because Anies Baswedan didn’t use longer pauses and delay, used faster turn-taking, gives more stories, active speaker, and produces expected answer. In a talk show, a host must be dominant in expressing ideas, opinions, or questions to the guest star. So, the speaker can freely express their thoughts and answer any questions asked by the host properly. The conversational style of an active, precise, and interesting host will also produce good responses from the guest star.